Praktik Administrasi Pekerjaan Sosial dalam Manajemen Pelayanan Sosial - Yolandika Arsyad; Rahmawati Rahmawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Social service management is an essential component in the implementation of social welfare programs, particularly within government-based social service institutions. This study aims to analyze the practice of social work administration in managing social services at the Social Affairs Office of Gorontalo City. The study employed a qualitative descriptive approach through in-depth interviews, observation, and documentation studies. Research informants consisted of administrative officials, staff members, and social assistance facilitators involved in the implementation of social service programs. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that social work administration practices in social service management are reflected through planning, organizing, decision-making, delegation, coordination, and priority-setting processes in service delivery. These administrative practices are also influenced by institutional structures, inter-agency coordination, and the implementation of centrally designed social welfare programs. This study concludes that social work administration plays an important role in supporting the effectiveness of social services within local government institutions. Therefore, strengthening administrative capacity, cross-sectoral coordination, and the development of social service innovations are necessary to support more responsive and sustainable social welfare services.